An atypical ALS with PSP-like symptoms caused by ANXA11 p.D40G mutation: A case report and literature review - Zhang, Xin; Gao, Juan; Chi, Chunling; Zhao, Zhenzhen; Chan, Piu; Ma, Jinghong (Frontiers in Neurology, 2023)
Background ANXA11 mutations were first reported to be associated with amyotrophic lateral sclerosis (ALS) in 2017. Several studies have investigated the prevalence of ANXA11 mutations in different populations, while less is known about the spectrum of phenotypes and the genotype–phenotype correlation with this gene mutation. Case presentation Here, we report a 74-year-old man who was initially diagnosed with progressive supranuclear palsy (PSP) because of repeated falls, slight upward gaze palsy, and mild cognitive dysfunction at the onset. He finally turned out to be ALS with more and more prominent limb weakness and atrophy, together with the evidence of chronic neurogenic change and ongoing denervation on electromyography. Brain magnetic resonance imaging showed extensive cortical atrophy. A missense mutation c.119A > G (p.D40G) on the ANXA11 gene was identified using whole-exome sequencing, which confirmed the diagnosis of ALS. We performed a systematic review of the literature about ALS-relevant cases with ANXA11 mutations and identified 68 affected subjects and 29 variants with the ANXA11 gene. We summarized the phenotypes of ANXA11 mutations and the clinical characteristics of nine patients harboring the ANXA11 p.D40G variant including our case. Conclusions The phenotype of ANXA11-related cases is heterogeneous, and most cases showed typical ALS, while some could also have the characteristics of frontotemporal dementia (FTD) and PSP, even inclusion body myopathies (hIBM) occurred in familial ALS (FALS). Our patient presented with ALS with a co-morbid PSP-like symptom (ALS-PSP) phenotype, which has not been reported. Except for our patient, the remaining eight patients with the ANXA11 p.D40G variant presented with a classical ALS phenotype without cognitive impairment.